(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
This article provides a morphological description of the species of the genus Berberis found in Kyrgyzstan, according to their geographical distribution